ORGANIZATIONAL ADAPTATION STRATEGIES CONFRONTING ENVIRONMENTAL UNCERTAINTY IN THE MODERN BUSINESS ERA - Sentoso, Antony; Sebastian, Sebastian; Setyawan, Agustinus (LPPM STIE Muhammadiah Bandung, 2024)
In an era of business characterized by uncertainty and rapid change, organizations are required to adapt and innovate to maintain their relevance and competitiveness. This article focuses on the relationship between environmental uncertainty, organizational agility, and innovation in the hotel industry. The aim of this research is to analyze how technological developments, external factors, and adaptation strategies influence an organization's ability to cope with environmental uncertainty. We also explore the role of information technology and data analysis in helping organizations enhance their responsiveness to the changing dynamics of the business environment. The results of this research provide valuable theoretical and practical insights for organizational leaders and business practitioners to develop effective adaptation strategies and improve organizational performance in facing the challenges of a dynamic business environment.